Nilai-Nilai Motif Songket Bengkalis Dalam Perspektif Pendidikan - Istiqomah, Nur; Indah Permata, Dian; Syahira, Syarifah (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
Bengkalis is also one of the districts with quite a lot of immigrant communities as a result of which there is a lot of cultural mixing. And there are not a few people who follow the culture brought by migrants, so that it can trigger the songket weaving craft to be less appreciated by the local community. This research will discuss 5 songket weaving motifs which are quite familiar among the people, especially the people of Bengkalis. Which aims to find out what educational values are contained in it. The research method used is descriptive qualitative method. Data collection techniques used in this research are observation, interviews and literature or documentation studies. While the selection of informants using purposive sampling technique. The Bengkalis Malay songket woven fabric has a variety of woven motifs or patterns ranging from flora, fauna, nature and others. These motifs have meanings that describe how the perspective of human life. In Riau, it has four weaving centers, namely in Indragiri Hulu, Rokan Hilir, Bengkalis and Siak. Each of these areas has a different basic motive. In the Bengkalis area, there are about 90 typical Malay motifs. In this study, five motifs that are well known among the public will be discussed, namely the bamboo shoots, ducks returning home, sentorak, elbow clouds and ants along. Riau Malay woven fabric is a fabric made by the handicrafts of the Malay people, which is done by the process of weaving threads interspersed with woven gold or silver threads with a certain variety of woven motifs or patterns. The variety of motifs and patterns of woven fabrics in Bengkalis is very diverse. And in each of these motifs there is a very close relationship between humans and nature, both animals and plants. For the Malays, the pattern is not only a mere decoration, but also used as a symbol or symbol that contains a certain meaning and philosophy which contains the noble values of the local culture